A Review of Paroxetine for the Treatment of Vasomotor Symptoms. (June 2015) - Slaton, Rachel M.; Champion, Megan N.; Palmore, Kayla B.
Background: Studies in recent years have exposed concerns about the safety of hormone replacement therapy (HRT) in the treatment of vasomotor symptoms (VMS) in menopausal women. Numerous studies have examined the use of antidepressants for relief of VMS. Despite recommendations to deny approval of paroxetine mesylate (Brisdelle™) for the treatment of VMS, the Food and Drug Administration (FDA) recently granted it approval for this indication. Objective: To evaluate all published literature examining use of paroxetine salts (mesylate and hydrochloride) in the treatment of menopausal VMS. Methods: Both PubMed and International Pharmaceutical Abstracts (IPA) were searched using the keywords hot flashes, vasomotor symptoms, menopause, and paroxetine. In PubMed, MeSH terms were used for paroxetine, menopause, and hot flashes. Searches were limited to humans, English language, and clinical trial design. The references for each study identified in this search process were examined in order to locate any additional relevant articles. Results: Compared with placebo, paroxetine salts offer a modest benefit in the treatment of menopausal VMS reducing the frequency and severity of weekly hot flashes. Conclusion: Paroxetine (mesylate or hydrochloride) is an effective alternative to HRT for the reduction in VMS in menopausal women. Future head-to-head studies with active medications are needed in order to identify the best algorithm of treatment for this condition.